2021
DOI: 10.1111/1749-4877.12528
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and immunological effects of gut microbiota in leaf beetles at the local and systemic levels

Abstract: Insects' intestinal microbes have profound effects on the host's physiological traits, which can impact their physiology at both the local (gut) and systemic (body) levels. Nevertheless, the molecular mechanisms underlying hostmicrobiota interactions, especially in non-model insects, remain elusive. Recently, tissue-specific transcriptomic analysis has been highlighted as a robust tool in studying host-microbe interactions. Plagiodera versicolora is a worldwide leaf-eating pest that primarily feeds on willows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…However, a high-DF diet can indirectly influence the digestibility of energy, amino acids, and other nutrition (19). As most of these small metabolites are closely related to host health and growth performance (10,18,20), determining the variation in microbial metabolites across different graded levels of DF diets could add to the available information for improving animal health and production. Liquid chromatography-mass spectrometry (LC-MS) is a popular tool for metabolomics analyses to determine the non-targeted profiles of a vast number of small metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high-DF diet can indirectly influence the digestibility of energy, amino acids, and other nutrition (19). As most of these small metabolites are closely related to host health and growth performance (10,18,20), determining the variation in microbial metabolites across different graded levels of DF diets could add to the available information for improving animal health and production. Liquid chromatography-mass spectrometry (LC-MS) is a popular tool for metabolomics analyses to determine the non-targeted profiles of a vast number of small metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…To promote integrative studies on this topic among scientists of different disciplines and exchange scientific research work of different species, Integrative Zoology published a special subsection on Intestinal microbiome in animals in May 2021. Authors shared their progress not only in vertebrates including Indo-Pacific humpback dolphin Sousa chinensis (Wan et al 2021), whales (Globicephala macrorhynchus and Kogia breviceps) (Bai et al 2021) and forest musk deer Moschus berezovskii (Li et al 2021) but also in invertebrate such as a willow leaf beetle Plagiodera versicolora (Ma et al 2021). The results showed that gut microbial communities varied in different species, anatomical regions, life stages, seasons, and environments.…”
Section: Intestinal Microbiota In Various Animalsmentioning
confidence: 96%
“…The gut microbiota is associated with many essential host physiological functions ( Sommer and Bäckhed, 2013 ; Xu et al, 2019 ; Grenier and Leulier, 2020 ). With the advent of sequencing technology, many bacteria impacting insect life activities have been found in the guts of a variety of insects ( Dillon et al, 2008 ; Hu et al, 2013 ; Fang et al, 2013 ; Ma et al, 2021 ). Some studies have focused on how insects adapt to different types of stress through gut microbes.…”
Section: Introductionmentioning
confidence: 99%